Oxidative stress in skin diseases and the role of antioxidants in their treatment - Vazhnichaya, E.M.; Baliuk, O.Ye.; Deviatkina , N.M.; Vlasenko , N.O.; Kovalev, S.V.; Bobrova, N.O. (Medicni Perspektivi, 2025)
More and more preclinical and clinical studies indicate the crucial role of oxidative stress in the pathogenesis of skin diseases. This became the basis for the analysis of current literature data on oxidative stress and antioxidant protection in the skin in the norm and dermatological diseases, as well as on the antioxidants use to manage this pathology.The aim of the study was to review the current literature on oxidative stress and antioxidant protection in the skin and to analyze the possibilities of using antioxidants in skin diseases. The search for literature sources for 2005-2025 was carried out in the biometric search engine PubMed using the terms: “oxidative stress”, “antioxidant”, “skin”, “skin disease”, “topical treatment”, “α-tocopherol”, “ascorbic acid”, “polyphenol”, “quercetin”, “coenzyme Q10”, “resveratrol”, “N-acetylcysteine”, as well as word combinations based on them. The inclusion criteria were: a document in English; publication in the period 2005-2025; compliance with search queries; availability of the article full text. The exclusion criteria were: a case from practice; conference proceedings; a publication that does not meet the purpose of the review; lack of full text, reflection of skin manifestations of a systemic disease or infection. The maximum number of literature sources was found for the query “oxidative stress – antioxidant – skin” (n=3076). After systematizing the selected documents using bibliographic and analytical methods, 115 of the most relevant sources remained. It was shown that the suppliers of reactive oxygen species (ROS) in the skin are processes that occur in keratinocytes, fibroblasts, and hematogenous cells. Many antioxidants eliminate ROS in the skin, they act together with superoxide dismutase, catalase, glutathione peroxidase and non-enzymatic antioxidants. Disruption of the balance between ROS and the power of antioxidant protection, i.e. oxidative stress, accompanies contact dermatitis, urticaria, atopic dermatitis, psoriasis, malignant skin tumors, photoaging, and vitiligo. The contribution of key natural antioxidants (ascorbic acid, α-tocopherol, retinoids, coenzyme Q10, resveratrol, selenium, and polyphenols) to skin care has been described, but there was only a small number of evidence-based studies that would justify the dosage and indications for their use in dermatology. Synthetic antioxidants are represented by almost one N-acetylcysteine in the treatment of toxic epidermal necrolysis, drug hypersensitivity syndrome, ichthyosis, contact and atopic dermatitis and some other diseases. The topical use of antioxidants is complicated by the search for an adequate dosage form, in which the stabilization of a substance with antioxidant properties is crucial, as well as its absorption, the ability to reach the target tissue in an active form and remain there for a long enough time, which is solved by the use of new methods of drug delivery, in particular based on nanotechnology. Thus, changes in the redox balance are widely represented in dermatoses, and the use of antioxidants can be of great importance if they are prescribed rationally. Obviously, it is advisable to combine antioxidants with each other and to introduce synthetic antioxidants more widely into practice.